Penerapan Model Pembelajaran TGT (Teams Games Tournament) dengan Permainan Ludo terhadap Hasil Belajar Siswa - Uswatun Hasanah; Rica Wijayanti; Metty Liesdiani (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2020)
The purpose of this study is to describe student learning outcomes after the teacher applies the TGT (Teams Games Tournament) learning model with ludo games. This research was conducted at MA Raudlatul Ulum Klampis on class X-MIA students, amounting to 24 even semester students. This research is quantitative descriptive. For data collection using research instruments in the form of student learning outcomes test sheets. The data collected in this study were test data on student learning outcomes after participating in the learning process using the test method. After the data was obtained, the data that had been collected were analyzed using descriptive analysis techniques, namely the analysis of student learning outcomes tests which were analyzed using the completeness of individual learning outcomes and classical learning outcomes. Students are said to be complete individually if they get a value of ≥65 and a class is said to be classically complete if they get KKM in the class totaling ≥65%. The conclusion of this study is that the application of the TGT learning model with the game of Ludo has an effect on student learning outcom